(untitled) (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2025)
Benign salivary gland tumors represent a heterogeneous group of neoplasms that vary in origin, histological structure, and clinical manifestations. This paper examines the key clinical and morphological features of the most common types of benign salivary gland tumors, including pleomorphic adenoma, monomorphic adenoma, basal cell adenoma, and others. Particular attention is paid to immunohistochemical markers used for differential diagnosis of these tumors. Research methods are described that allow for accurate determination of the nature of the tumor and selection of optimal treatment strategies. This paper is intended for specialists in oncology, pathology, and maxillofacial surgery.